Spatiotemporal variations in integrated trophic positions of stream macroinvertebrate communities - Naoto F. Ishikawa; Yoshitoshi Uehara; Takuya Ishida; Tohru Ikeya; Satoshi Asano; Chia-Ying Ko; Tomoya Iwata; Ichiro Tayasu; Naohiko Ohkouchi; Noboru Okuda (Progress in Earth and Planetary Science)
Abstract To understand energy and material cycles on surface Earth, it is important yet challenging to estimate trophic transfer through ecosystems. To address this issue, the integrated trophic position (iTP), defined as a biomass-weighted average TP of a given food web, is useful because the iTP can be a proxy for the configuration of ecological pyramid. Here we conducted the compound-specific nitrogen isotope analysis of amino acids for macroinvertebrate communities collected from the Ado and Yasu Rivers in the Lake Biwa watershed, Japan, to estimate their iTP values. Unlike previous studies, no clear relationships between iTP and biodiversity (Shannon index H’) were found. However, by comparing the irrigated period and the non-irrigated period within the Yasu River, the decrease in iTP values was fairly characterized by the increase in H’. A significant difference in the observed iTP values compared to those reported in the previous study suggests that the configuration of ecological pyramid in stream ecosystems is dynamic rather than static. We also found that the iTP values of stream macroinvertebrate communities (2.37 ± 0.24) (n = 43), marine mesozooplankton communities (2.33 ± 0.34) (n = 14), and animal communities with various taxonomic groups (2.42 ± 0.21) (n = 158) are all comparable with each other, suggesting that partial communities involving macroinvertebrates well represent the configuration of total ecological pyramid. This finding clearly delineates the promising performance of the iTP index for the trophic transfer of energy, which should be further explored in a variety of ecosystems.